Influencia del programa BLN de canal uno en el desarrollo de estereotipos socioculturales en adolescentes de entre 14 y 16 años del Centro Educativo Novus - Campuzano Jácome, Ashley Dennissé (2019)
The purpose of this study on “The influence of the media in adolescents” how much they affect themselves and how often they use them, one of them is the television media which young people spend most of their time, including social networks and one of them are reality show programs where they expose a mixture of science fiction of the participants with reality, situations of love, conflicts between participants, erotic dances and competitions that require strength. Those programs cause a distortion in the formation of each one of them, so the teenagers adopting stereotypes and inappropriate behaviors, because these reality shows transmit sexual postures and dances………